Hubungan Status Gizi dengan Stunting pada Balita - Yuningsih Yuningsih (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
Stunting is a growth and development problem in children that can result in morbidity, mortality, and decreased motor development. The incidence of stunting is often found in conditions that lack energy intake. Jember is the district with the highest stunting incidence rate in the East Java region in 2020. The working area of ​​the Kaliwates Jember Health Center has a stunting rate of around 460 at the age of 24-72 months. This research was observational with cross sectional approach. Taking non-random sampling of respondents using the N formula so that a sample of 82 was obtained and using statistical analysis using Chi Square. The results of data analysis of nutritional status with stunting in toddlers obtained a value (p value = 0.04) = 0.05, which means that there was a relationship between nutritional status and the incidence of stunting. The conclusion of this study is that there is a high incidence of stunting in the work area of ​​the Kaliwates Health Center in 2020 which has poor nutritional status and has a close relationship between these variables. Suggestions for parents to be able to maintain the health of toddlers as an effort to prevent and overcome stunting in toddlers.